2-D steering and propelling of acoustic bubble-powered microswimmers. Issue 12 (27th May 2016) - Feng, Jian; Yuan, Junqi; Cho, Sung Kwon
Abstract : This paper describes bi-directional (linear and rotational) propelling and 2-D steering of acoustic bubble-powered microswimmers that are achieved in a centimeter-scale pool (beyond chip level scale). Abstract : This paper describes bi-directional (linear and rotational) propelling and 2-D steering of acoustic bubble-powered microswimmers that are achieved in a centimeter-scale pool (beyond chip level scale). The core structure of a microswimmer is a microtube with one end open in which a gaseous bubble is trapped. The swimmer is propelled by microstreaming flows that are generated when the trapped bubble is oscillated by an external acoustic wave. The bubble oscillation and thus propelling force are highly dependent on the frequency of the acoustic wave and the bubble length. This dependence is experimentally studied by measuring the resonance behaviors of the testing pool and bubble using a laser Doppler vibrometer (LDV) and by evaluating the generated streaming flows. The key idea in the present 2-D steering is to utilize this dependence. Multiple bubbles with different lengths are mounted on a single microswimmer with a variety of arrangements. By controlling the frequency of the acoustic wave, only frequency-matched bubbles can strongly oscillate and generate strong propulsion. By arranging multiple bubbles of different lengths in parallel but with their openings opposite and switching the frequency of the acoustic wave, bi-directionally linear propelling motions are successfully achieved. The propelling forces are calculated by a CFD analysis using the Ansys Fluent® package. For bi-directional rotations, a similar method but with diagonal arrangement of bubbles on a rectangular swimmer is also applied. The rotation can be easily reversed when the frequency of the acoustic wave is switched. For 2-D steering, short bubbles are aligned perpendicular to long bubbles. It is successfully demonstrated that the microswimmer navigates through a T-junction channel under full control with and without carrying a payload. During the navigation, the frequency is the main control input to select and resonate targeted bubbles. All of these operations are achieved by a single piezoelectric actuator.